Metal-Size Influence in Iso-Selective Lactide Polymerization - Bakewell,C; White,AJP; Long,NJ; Williams,CK (Angewandte Chemie-International Edition, 2014)
Iso-selective initiators for the ring-opening polymerization (ROP) of rac-lactide are rare outside of Group13. We describe the first examples of highly iso-selective lutetium initiators. The phosphasalen lutetium ethoxide complex shows excellent iso-selectivity, with a Pivalue of 0.81–0.84 at 298K, excellent rates, and high degrees of polymerization control. Conversely, the corresponding La derivative exhibits moderate heteroselectivity (Ps=0.74, 298K). Thus, the choice of metal center is shown to be crucial in determining the level and mode of stereocontrol. The relative order of rates for the series of complexes is inversely related to metallic covalent radius: that is, La>Y>Lu.